Service quality of provincial land transport office of Roi Et - Khruamingmongkhon, Narong; Phosing, Phakdee; Yupas, Yupaporn (Journal for Developing the Social and Community, 2021)
The objectives of this research were to study level of opinion about service quality of provincial land transport office of Roi Et.To compare of level of opinion about service quality and other suggesting. The study was conducted using 294 people, Sampling technique with Taro Yamane method. The research instruments was a rating - scale questionnaire. The statistics used percentage , mean , frequency , standard deviation (SD) and Compared personal factor of gender and using statistic T- test and compared factors of age, educational level, living district using statistic One – way ANOVA The results of research were as follow : 1) The overall of service quality of provincial land transport office of Roi Et was rated at a high level. 2) To compare of needs of service quality of provincial land transport office of Roi Et and classify by gender, age, educational level, living district were not difference. 3) The study also suggested : Should be staff available and able to provide a replacement. Should have service during the lunch break. Should be a property that is clean. Should be a variety of contact methods.